Endoplasmic reticulum–plasma membrane junctions: structure, function and dynamics. (7th May 2016) - Okeke, Emmanuel; Dingsdale, Hayley; Parker, Tony; Voronina, Svetlana; Tepikin, Alexei V.
Abstract : The 'mature' junction (shown on the right) is STIM1‐competent and is hypothetically developed from a nascent junction (shown on the left) following the initial contact between oligomerized STIM1 (anchored in the ER) and the PM. In the mature junction STIM1 interacts with Orai1 and with adenylyl cyclase 3 (AC3, possibly via an adaptor protein). Adenylyl cyclase 8 (AC8) interacts with Orai1 and is sensitive to local SOCE‐induced Ca 2+ microdomains. SERCA pumps have been shown to localise in the ER–PM junctions and coordinate their transport activity with SOCE. Lipid transporters Nir2 and Nir3 localise in ER–PM junctions and directly transfer phosphatidylinositol from the ER membrane to the PM. Oxysterol‐binding protein‐related proteins 5 and 8 (ORP5 and ORP8) transfer phosphatidylinositol 4‐phosphate (PI4P) from the PM to the ER across ER–PM junctions; PI4P transport is coupled to the reverse transport of phosphatidylserine from the ER to the PM. After reaching the ER membrane PI4P can be dephosphorylated by Sac1 phosphatase. ER‐anchored protein‐tyrosine phosphatase 1B (PTP1B) can interact with some of its PM‐localised substrates in ER–PM junctions. The right part of the figure illustrates hypothetical tethering of the mitochondrion to both ER and PM membranes (depicted by grey and black rods correspondingly) and a mitochondrion is shown in proximity to the mature ER–PM junction. Septins are not localised in the mature STIM1‐competent ER–PM junctions but can temporarily translocate to the neighbourhood of the junctions and influence the distribution of the PM phoshoinositides, Orai1 clustering and STIM1–Orai1 interaction in the junctions. Abstract: Endoplasmic reticulum (ER)–plasma membrane (PM) junctions are contact sites between the ER and the PM; the distance between the two organelles in the junctions is below 40 nm and the membranes are connected by protein tethers. A number of molecular tools and technical approaches have been recently developed to visualise, modify and characterise properties of ER–PM junctions. The junctions serve as the platforms for lipid exchange between the organelles and for cell signalling, notably Ca 2+ and cAMP signalling. Vice versa, signalling events regulate the development and properties of the junctions. Two Ca 2+ ‐dependent mechanisms of de novo formation of ER–PM junctions have been recently described and characterised. The junction‐forming proteins and lipids are currently the focus of vigorous investigation. Junctions can be relatively short‐lived and simple structures, forming and dissolving on the time scale of a few minutes. However, complex, sophisticated and multifunctional ER–PM junctions, capable of attracting numerous protein residents and other cellular organelles, have been described in some cell types. The road from simplicity to complexity, i.e. the transformation from simple 'nascent' ER–PM junctions to advanced stable multiorganellar complexes, is likely to become an attractive research avenue for current and future junctologists. Another area of considerable research interest is the downstream cellular processes that can be activated by specific local signalling events in the ER–PM junctions. Studies of the cell physiology and indeed pathophysiology of ER–PM junctions have already produced some surprising discoveries, likely to expand with advances in our understanding of these remarkable organellar contact sites.